2017
DOI: 10.1063/1.4974849
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-wideband cross polarization conversion metasurface insensitive to incidence angle

Abstract: A broadband microwave cross-polarization-conversion (CPC) metasurface is designed, simulated, fabricated, and tested. The metasurface consists of coupled split-ring-resonators (SRRs) with two splits in each SRR and is designed on an FR4 dielectric substrate backed by a metallic ground plane. An efficient CPC, both for normal as well as for oblique incidence, is achieved with 3 dB fractional bandwidth of 73% from 5 to 10.8 GHz. This wideband polarization conversion results from multiple plasmonic resonances occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(82 citation statements)
references
References 19 publications
0
79
0
3
Order By: Relevance
“…We see from the figure that R yx is above −3 dB, whereas R xx is below −10 dB at 15.25 and 17.35 GHz. Thus, when a linearly polarized EM wave incidents on such a structure horizontally (or vertically), it gets reflected as a linearly polarized wave with its polarization orthogonal to that of the incident wave . From Figure , it is clearly observed that the PCR is above 80% at the two frequencies mentioned above.…”
Section: Analysis Of the Multifunctional Metasurfacementioning
confidence: 90%
“…We see from the figure that R yx is above −3 dB, whereas R xx is below −10 dB at 15.25 and 17.35 GHz. Thus, when a linearly polarized EM wave incidents on such a structure horizontally (or vertically), it gets reflected as a linearly polarized wave with its polarization orthogonal to that of the incident wave . From Figure , it is clearly observed that the PCR is above 80% at the two frequencies mentioned above.…”
Section: Analysis Of the Multifunctional Metasurfacementioning
confidence: 90%
“…Polarization converter can be realized in different ways. In the past decade, it has be found that frequency selective surface (FSS) and metasurface can provide a convenient way to control the polarization state of a EM waves, now different types of polarization converters, such as cross polarization converters, [2][3][4][5][6][7][8][9][10][11][12] and linear-to-circular polarization converters, [13][14][15][16][17][18][19][20][21][22][23] have been realized using various FSSs or metasurfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Based on various MMs, many different polarization converters have been proposed , and they were usually realized in one of the following two methods: one is to divide a LP wave into two orthogonal components and generate a different phase between them (the fundamental of birefringence effect) by using anisotropic MMs, and the other is to mimic molecule chirality (the fundamental of optical activity) by using chiral MMs. The existing literature indicates that anisotropic two-dimensional MMs (also called metasurfaces) are more suitable for the design of reflective polarizers, and now a number of high-efficiency and ultra-wideband reflective linear polarizers were achieved by using multiple plasmon resonances of different anisotropic metasurfaces [4][5][6][7][8][9][10][11][12][13][14]. However, chiral MMs are convenient for designing transmissive polarizers.…”
Section: Introductionmentioning
confidence: 99%